Interface engineering of amorphous boron for high-efficiency interfacial solar steam generation. (14th December 2022) - Yang, Bo; Feng, Ying; Wang, Wenjing; Zhang, Min; Kong, Xiangkai; Liu, Qiangchun; Xu, Haifeng; Yao, Jixin; Li, Guang; Guo, Sheng-Qi
Abstract : We investigate interface regulation of amorphous boron and cotton pads to experimentally verify their performance in solar steam generation. Thanks to the superabsorbent cotton pads and the construction design, unobstructed water flow is achieved. Abstract : Solar steam generation that can directly harness solar energy to produce clean water from undrinkable water resources offers great application prospects in water purification systems. An open question remains though on how to improve the evaporation efficiency by choosing and optimizing a suitable candidate material system. Herein, we demonstrate experimentally that interface regulation of amorphous boron and cotton pads brings about high performance for solar steam generation. In this study, amorphous boron after surface treatment was well combined with cotton sheets, realizing a stable interfacial photothermal evaporation structure. Besides, the benefits from the superabsorbent cotton pads and the structure, provides an unobstructed water transport channel, which is conducive to the generation and circulation of vapor. Taking advantage of the above synergies, the system achieved a high evaporation rate of 2.43 kg m −2 h −1 under 1 kW m −2 solar illumination. The amorphous boron interfacial heating evaporator achieved a high energy efficiency of 95.3% under 1 sun irradiation. We anticipate that the results not only demonstrate the effectiveness of interface engineering in solar steam generation design but also provide a facile and cost-effective strategy applicable for water purification.